(untitled) (Global Journal of Medical Research, 2023)
Background The primary function of small bowel is digestion and absorption of dietary components after they leave the stomach The enlarged surface area of small intestine enables complete digestion of food stuffs Investigators has correlated the length of small bowel with age gender height and weight The aim of study To asses intraoperatively the small bowel length measurements and analysis of demographic predictors of increased length Patients and methods This cross-sectional study was conducted in Emergency Department of Cairo University hospital from January 2021 to June 2021 We included 160 patients who have been admitted to general surgery department of KasrAlainy who were indicated for abdominal surgery Measurement the of the small bowel is expressed in centimeters starting at ligament of Treitz and ending at the ileocecal junction using a sterile 10 cmtape applied to the antimesenteric border of un stretched small intestine